2002
DOI: 10.1089/152308602753666325
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Endogenous Carbon Monoxide Formation in Biological Systems

Abstract: Endogenous carbon monoxide (CO) formation has been measured in different biological systems using a variety of analytical procedures. The methods include gas chromatography-reduction gas detection, gas chromatography-mass spectroscopic detection, laser sensor-infrared absorption, UV-visible spectrophotometric measurement of CO-hemoglobin or CO-myoglobin complex, and formation of (14)CO from (14)C-heme formed following [2-(14)C]glycine administration. CO formation ranged from a low of 0.029 nmol/mg of protein/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 23 publications
0
41
1
1
Order By: Relevance
“…CO is known to autoinhibit HO and thus its own synthesizing enzyme. While endogenous CO does not inhibit HO reaction (Marks et al 2002), larger amounts of exogenous CO attenuated this reaction (Yoshida et al 1980). Nevertheless, the reported vasodilatory effects of other studies (Hartsfield et al 2004;Nishikawa et al 2004;Kanu et al 2006;Hosgood et al 2008) could not be observed in this experiment.…”
Section: Co Under Physiological Conditionscontrasting
confidence: 72%
“…CO is known to autoinhibit HO and thus its own synthesizing enzyme. While endogenous CO does not inhibit HO reaction (Marks et al 2002), larger amounts of exogenous CO attenuated this reaction (Yoshida et al 1980). Nevertheless, the reported vasodilatory effects of other studies (Hartsfield et al 2004;Nishikawa et al 2004;Kanu et al 2006;Hosgood et al 2008) could not be observed in this experiment.…”
Section: Co Under Physiological Conditionscontrasting
confidence: 72%
“…Therefore, the carboxyhaemoglobin concentration in the subject is a good marker of endogenous HO activity. 27 Furthermore, it has been reported that HO-1 is strongly induced in patients with bacterial infection. 28 We have already shown that arterial carboxyhaemoglobin increases at the onset of pneumonia in untreated patients returns to baseline on recovery after treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The combination rate of NO with hemoglobin is faster and dissociation is slower than that of CO (Sharma and Ranney, 1978), so that the affinity of NO for hemoglobin is ∼1,500-times that of CO (Foresti and Motterlini, 1999). Formation of endogenous CO in a variety of tissues has been demonstrated (Marks et al, 2002). Given the complexity of colocalization and activities of heme oxygenase and nitric oxide synthase, it has been speculated that "CO and NO could function in a synergistic, compensatory, and/or counterregulatory way" (Hartsfield, 2002).…”
Section: Physiological Roles Of Carbon Monoxidementioning
confidence: 99%